Pemberdayaan UMKM Kampoeng Batik Jetis Kabupaten Sidoarjo melalui Strategi Branding Pada Era Disrupsi - Artanto, Aphief Tri; Pratama, Arista; Sukirmiyadi, Sukirmiyadi; Kusnarto, Kusnarto; Sholihatin, Endang Sholihatin (Universitas Airlangga, 2021)
Micro, small and medium enterprises (MSMEs) play an important role in economic development because of their considerable contribution to job creation and improving people's welfare. Problems that often arise in MSMEs include limited capital, lack of innovation, conventional marketing, inefficient financial management, weak branding, lack of innovation, not maximizing online marketing due to technological stuttering. This research focuses on empowering MSMEs for branding strategies in competitive batik products in order to win the market based on the concept of blue ocean strategy. This study used qualitative research methods. The research location is Kampoeng Batik Jetis, Sidoarjo Regency. Data were collected through in-depth interviews, documentation studies, and observations. The unit of research analysis is the individual level of MSME actors. This research is a descriptive qualitative research. The data analysis of this study used qualitative data analysis techniques following Miles and Huberman. Conclusion Branding strategy on batik product competition in order to be able to win the market based on the concept of blue ocean strategy by: (a) added value (b) creating and (c) enhancing features and benefits. Usaha mikro, kecil, dan menengah (UMKM) memainkan peran penting pembangunan ekonomi karena kontribusinya yang cukup besar terhadap penciptaan lapangan kerja dan meningkatkan kesejahteraan masyarakat. Persoalan yang kerap muncul pada UMKM diantaranya adalah terbatas modal, kurang inovasi, pemasaran konvensional, pengelolaan keuangan tidak efisien, branding yang lemah, kurangnya inovasi, belum memaksimalkan pemasaran online karena gagap teknologi. Penelitian ini memfokuskan pada pemberdayaan UMKM untuk strategi branding pada persaingan produk batik agar memenangkan pasar berdasarkan konsep blue ocean strategy. Penelitian ini menggunakan metode penelitian kualitatif. Lokasi penelitian di Kampoeng Batik Jetis Kabupaten Sidoarjo. Data dikumpulkan melalui wawancara mendalam, studi dokumentasi, dan observasi. Unit analisis penelitian adalah tingkatan individu pelaku UMKM. Penelitian ini adalah penelitian kualitatif deskriptif. Analisis data penelitian ini menggunakan teknik analisis data kualitatif mengikuti Miles dan Huberman. Kesimpulan Strategi branding pada persaingan produk batik agar mampu memenangkan pasar berdasarkan konsep blue ocean strategy dengan: (a) nilai tambah (b) menciptakan dan (c) peningkatan fitur dan manfaat.